Plorantis Croatiae saecula duo: discursive adaptations and performative functions of the baroque stabat mater topos - Blažević, Zrinka (2003)
Plorantis Croatiae saecula duo is a little known lyric-epic poem by Croatian poet and polymath Pavao Ritter Vitezović (1652-1713), published in Zagreb in 1703. The poem has an interesting narrative structure because a personified Croatia describes its own history during the 16th and 17th century, marked by Ottoman conquests. The most prominent feature of Vitezović&#8217 ; s poetic discourse is the gender rift between the author and the enunciatory subject, the personified Croatia-patria, metaphorically identified with woman-mother. Narrating in the first person, Croatia presents a kind of &#8216 ; egohistory of mourning&#8217 ; during the two centuries of Ottoman conquests. This renders the whole poem an exercise in the form of (pseudo)autobiography and at the same it is time an allegorical allusion to the stabat mater topos. My aim will be identifying Vitezović's poetic procedures and narrative strategies, respectively, features of the discursive adaptations of that topos. Putting the poem in its broader political and cultural context I attempt to examine the ideological connotations and performative functions of the adapted stabat mater topos ranging from the affective profession of the baroque pietas and expressing loyalty to the ruler to the mobilizing patriotic audience for the anti Ottoman war of liberation.
Projekt MZOS
ENG